Sexually Transmitted Diseases (STDs) and Sexual Health in Costa Rica Topic I. HIV / AIDSl - Gutiérrez-Sandí, William (2016)
STDs are caused by more than 30 bacteria, viruses and parasites different, and mostly spread by sexual contact, including vaginal, anal and oral sex.Some STDs can be spread by skin sexual contact. STD-causing organisms can also spread by non-sexual means, for example, blood product transfusions and tissue transplants. Many STDs, especially chlamydia, gonorrhea, hepatitis B, HIV, HPV, HSV-2 and syphilis, can also be transmitted from mother to child during pregnancy and childbirth.A person may have an STD without showing symptoms of illness. Therefore, the term “sexually transmitted infection” is broader than “sexually transmitted disease” (STD). Common symptoms of STDs include vaginal discharge, urethral discharge in men, genital ulcers and abdominal pain.Among the more than 30 known pathogens are transmitted by sexual contact, eight have been linked to high incidence of diseases. Of those eight infections, four are currently curable, namely, syphilis, gonorrhea, chlamydia and trichomoniasis. Four, other hepatitis B, herpes, HIV and HPV are incurable viral infections, however, they can mitigate or lessen with treatment.This study is being communicated in three volumes where the most common bacterial, viral, fungal be covered, as well as habits and care that should have people who maintain an active sex life not to be infected by an STD.In this first installment will be developed the theme of HIV / AIDS and its impact at global, regional and national levels. Therefore, each of the subsequent deliveries will complement the previous number, so you can go instructing the reader in the care and management of each condition described.